Subsidiariedad y tribunales internacionales de derechos humanos: ¿deferencia hacia los estados o división cooperativa del trabajo? - Iglesias Vila, Marisa (2017)
In this article I develop a normative theory of the subsidiarity principle in international adjudication, which seeks to offer a balanced answer to the question of to what extent is it legitimate for a body such as the European Court of Human Rights to interfere with the national criteria in the face of a complaint on conventional rights violation. In contrast with demands for greater deference to states in both Europe and Latin America, based on a statist idea of subsidiarity, I articulate a «cooperative» understanding of the ideas of human rights and the principle of subsidiarity, linking them to Buchanan’s notion of ecological legitimacy. The proposal I defend leads to a division of institutional labor within regional human rights systems that increases the legitimacy of all the institutions involved. At the same time, I devote the last part of the paper to implement such cooperative view, on the one hand, showing the importance of an incremental logic in the effective protection of human rights and, on the other hand, offering a rationalized version of the national margin of appreciation doctrine.